PENGARUH KUNJUNGAN WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN SUMBAWA BARAT - Rista Azizah; Erwin Ramdani; Subhan Purwadinata (Pusat Riset dan Publikasi, 2022)
This study aims to determine the effect of the number of tourist visits on the Regional Income (PAD) of West Sumbawa Regency in 2017-2021. The type of this research is associative. The type of data used is quantitative, obtained from secondary sources in the form of documents obtained from the Tourism Office and the Central Statistics Agency of West Sumbawa. The data that has been collected is processed using the SPSS program, then analyzed using simple linear regression analysis techniques, partial test (t test), and coefficient of determination test (R2). The results of this study indicate that the number of tourist visits has a positive and significant impact on the Regional Income (PAD) of West Sumbawa Regency in 2017-2021. The ability of the variable Number of Tourist Visits in influencing changes in the Regional Income (PAD) of West Sumbawa Regency is 93.8%, while the remaining 6.2% is influenced by other variables not examined, such as the results of regional wealth, regional taxes, regional levies and so on.